Spontaneous hematometra: a rare cause of pain lower abdomen - Manandhar, Rojina; Singh, Asha; Shrestha, Abhimanyu; Shrestha, Sebak (Nepal Journal of Obstetrics and Gynaecology, 2019)
Hematometra is a rare condition that is most commonly associated with congenital anomalies and prior surgical procedures. This is an unusual case of spontaneous hematometra occuring in 32 years old healthy woman with no prior medical or surgical history. Till now only five cases of spontaneous hematometra without any risk factors have been reported. Keywords: abdominal pain, depot medroxyprogesterone acetate, hematometra